• Предмет: Математика
  • Автор: belckovaleria
  • Вопрос задан 6 лет назад

1,Упростите выражение −4(2,3x − 3) − (5 − 2,6x) + 3(0,6x − 2) и вычисли-
те его значение при x = 5/12

.2.Упростите выражение −2(2,7x − 1) − (6 − 3,4x) + 8(0,4x − 2) и вычисли-
те его значение при x = −5/6

это одно и тоже только цифры разные !!!!!!!!!!!

Ответы

Ответ дал: kruglenkonata804
0

−4(2,3x − 3) − (5 − 2,6x) + 3(0,6x − 2) =

=-9,2х+12-5+2,6х+1,8х-6=-4,8х+1

x = 5/12

-4,8*5/12+1=-4 8/10*5/12+1=-4 4/5*5/12+1= -24/5*5/12+1=-2+1=-1

−2(2,7x − 1) − (6 − 3,4x) + 8(0,4x − 2)=

=-5,4х+2-6+3,4х+3,2х-16=1,2х-20

х= −5/6

1,2*(-5/6)-20=1 2/10*(-5/6)-20= 1 1/5*(-5/6)-20=6/5*(-5/6)-20=-1-20=-21

Ответ дал: belckovaleria
0
спасибо
Похожие вопросы